Analisis Penerapan Audit Manajemen Sumber Daya Manusia Dalam Meningkatkan Efektivitas Kinerja Karyawan di PT. Mattel Indonesia - Irmayanti, Ika; Rismayadi, Budi; Pertiwi, Wike (JURNAL ADMINISTRASI & MANAJEMEN, 2023)
The purpose of this research is to see the effectiveness of employee performance and provide suggestions and recommendations from the findings of the human resource audit at PT Mattel Indonesia. This research is a descriptive qualitative research using data collection methods of interviews and questionnaires to the human resource management division. The data analysis method used is qualitative analysis using the interactive analysis model from Miles and Huberman which is divided into 4 major parts, namely data collection, data reduction, data presentation, conclusion drawing and verification. The results showed that the management of PT Mattel Indonesia does not yet have procedures governing HR planning, therefore it is necessary to have quality HR planning. Some HR function activities at PT Mattel Indonesia have been running effectively, including HR recruitment, HR selection and placement, HR training and development, career planning and development, employee performance appraisal, service compensation, labor relations, occupational health and safety, employee job satisfaction, termination of employment.